Hubungan Partisipasi Anggota Dengan Keberhasilan Usaha Koperasi KOPRIMPU BINA MARGA Kementerian Pekerjaan Umum Dan Perumahan Rakyat Jakarta - Sarji; Gemina, Dwi; Kartini, Tini (Karimah Tauhid, 2022)
This study aims to analyze the relationship between member participation and the business success of the KOPRIMPU BINA MARGA Cooperative, Ministry of Public Works and Public Housing, Jakarta. The object of this research is the members of the cooperative and the questionnaires were distributed to 100 respondent members. The research method used is descriptive and associative methods. The test carried out is the validity test and reliability test with the results showing valid and reliable. The results of the test with SPSS 2, the correlation between member participation and business success showed that the relationship between member participation and business success at KOPRIMPU Bina Marga showed an R value of 0.763 which was included in the strong and positive category.